PENGARUH PENDEKATAN KONTEKSTUAL TERHADAP KEMAMPUAN MENGANALISIS KAIDAH KEBAHASAAN TEKS PROSEDUR PADA SISWA KELAS XI MA INTEGRAL HIDAYATULLAH MANOKWARI - Elvi Rahmi (LP4MK STKIP PGRI Lubuklinggau, 2022)
This study aims to determine the ability of Class XI MA Integral Hidayatullah Manokwari students in analyzing the linguistic rules of procedure text. This type of research is a quasi-experimental carried out without a comparison group or class. The population in this study were all students of class XI and as a sample the experimental class was class XI MIPA 1 as many as 32 students. Sampling in this study was done randomly (simple random sampling) by lottery. Data was collected by using a written test technique. Student test score data were analyzed using t-test. Based on the results of hypothesis testing with a significant level of α = 0.05, it was obtained tcount > ttable = (4.86> 2.00) which means H0 is rejected and Ha is accepted. So it can be concluded that the students' ability to analyze the linguistic rules of the procedure text after applying contextual learning is significantly increased.